THE INFLUENCE OF CURCUMIN NANOEMULSION DROPLET SIZE ON PHARMACOKINETIC PROFILE CURCUMIN AFTER INTRAVENOUS AND ORAL IN MALE WISTAR RATS - Meylina, Lisna
Background and purpose: Curcumin shows low plasma concentration after oral administration due to poor absorption, rapid metabolism, and rapid systemic elimination. To improve the bioavailability of curcumin, numerous approaches have been developed. In previous research curcumin was formulated into nanoemulsion, aimed to improve the stability and absorption of curcumin. It is reported that particle size influences pharmacokinetic profile of the compound, therefore this research studied the effect of curcumin nanoemulsion droplets size on the pharmacokinetics of curcumin. Methods and Results: Glyceryn monooleate (GMO) as an oil, cremophor RH40 as a surfactant, and polyethylene glycol 400 (PEG 400) as a cosurfactant in ratio 1:8:1. Evaluation of curcumin nanoemulsion was carried out including to droplets size analysis, distribution droplets size, zeta potential, and loading efficiency. The pharmacokinetic profile of curcumin nanoemulsion in various sizes was studied to determine the relationship between particle size to the behavior in vivo by intravenous and oral. Rats were divided into 4 groups on intravenous administration (droplets size of 58,73 ± 1,02 nm; 146,17 ± 2,31 nm; 235,62 ± 2,34 nm; 304,89 ± 5,57 nm) and 5 group on oral (n=4) with a variation of the same droplets size as intravenous (groups 1-4) and emulsified curcumin (group 5). Nanoemusion dosage given by IV is 10 mg/kg bb and 50 mg/kg bb for oral administration. Blood samples were taken via the tail vein before the test substance and at 0,25; 0,5; 1; 2; 4; 8; 12; 24 after administration of curcumin nanoemulsion. Curcumin levels in plasma was determined by HPLC method. Results showed that the larger droplets size has the lower value of Cmax; AUC0-24; AUC0-?; as well as the value of tmax (the intravenous administration). Conclusion: Droplets size of curcumin nanoemulsion affects the pharmacokinetics of curcumin after intravenous as well as oral administrations i.e droplets size of nanoemulsion is inversely proportional to the bioavailability.